The meaning of labour pain: how the social environment and other contextual factors shape women's experiences - Laura Y. Whitburn; Lester E. Jones; Mary-Ann Davey; Rhonda Small (BMC, 2017)
Abstract Background The majority of women experience pain during labour and childbirth, however not all women experience it in the same way. In order to develop a more complete understanding of labour pain, this study aimed to examine women's experiences within the perspective of modern pain science. A more complete understanding of this phenomenon can then guide the development of interventions to enhance women's experiences and potentially reduce their need for pharmacological intervention. Methods A qualitative study was conducted using phenomenology as the theoretical framework. Data were collected from 21 nulliparous women, birthing at one of two large maternity services, through face-to-face interviews and written questionnaires. Data were analysed using an Interpretative Phenomenological Analysis approach. Results The data from this study suggest that a determining factor of a woman's experience of pain during labour is the meaning she ascribes to it. When women interpret the pain as productive and purposeful, it is associated with positive cognitions and emotions, and they are more likely to feel they can cope. Alternatively, when women interpret the pain as threatening, it is associated with negative cognitions and emotions and they tend to feel they need help from external methods of pain control. The social environment seems particularly important in shaping a woman's pain experience by influencing her interpretation of the context of the pain, and in doing so can change its meaning. The context and social environment are dynamic and can also change throughout labour. Conclusion A determining factor in a woman's experience of pain during labour is its perceived meaning which can then influence how the woman responds to the pain. The meaning of the pain is shaped by the social environment and other contextual factors within which it is experienced. Focussed promotion of labour pain as a productive and purposeful pain and efforts to empower women to utilise their inner capacity to cope, as well as careful attention to women's cognitions and the social environment around them may improve women's experiences of labour pain and decrease their need for pain interventions.